LEUCOCYTE CHANGES IN NORMAL PREGNANCY IN MAIDUGURI NORTH EASTERN NIGERIA - TUKUR MA; CHAMA C; ENYIKWOLA O; ADELAYE AB (Ntec Specialist, 2009)
Background: Medline search revealed paucity of data with respect to the leucocyte changes in normal pregnancy in Maiduguri. Objectives: to determine the normal range of leucocyte count in pregnancy and the effect of parity on leucocyte counts. Method a cross sectional study carried out at the University of Maiduguri Teaching Hospital (UMTH) Maiduguri between April - October 2005. The subjects were pregnant women at different gestational age recruited from the antenatal clinic at booking. The control groups were women from the family planning clinic who had weaned their babies and not on hormonal contraceptives. Blood samples were collected from the 200 normal pregnant women (cases) and 150 non-pregnant controls for blood cell count and differential. Result: the mean count for the white blood cell (WBC) was higher in prignancy. The values for total leucocyte count (TLC) were 7.9 +/- 2.05, 8.33 +/- 1.74, and 8.74 +/- 1.87 in the 1, 2 and 3 trimesters respectively. The mean differential leucocyte counts in the 1, 2 and 3 trimesters were neutrophils 2.98, 2.98 and 3.9; lymphocytes 2.95, 3.66 and 3.86 eosinophils 0.72, 0.84 and 0.92 and monocytes 0.72, 0.84 and 0.88 respectively. The values for the non-pregnant controls were TLC 7.82 +/- 1.11, neutrophils 1.95, lymphyhocyytes 4.2, eosinophils 0.78 and monocytes 0.78. There were no statistically significant differences between parity and TLC. Conclusion: There is a significant rise in total leucocyte count with increasing gestation age, but parity has no effect on leucocyte count.